Institutional Ijtihād and Socio-Legal Adaptation: The Formulation of Waṣiyah Wājibah in Indonesia’s Compilation of Islamic Law - Achmad Roziqi; Ramadhan, M. Rizki Syahrul; Ananda Prayogi; Falah, Fajrul (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
Studies of Islamic law in Indonesia have generally framed wasiat wājibah (mandatory will) merely as a normative innovation, without providing a comprehensive account of the epistemic processes and socio-cultural dialectics underpinning its formulation. This article examines the rationale behind wasiat wājibah in the drafting process as a form of institutional ijtihād (reasoning) responsive to the plural realities of Indonesian Muslim society. Employing a library-based method within a socio-legal framework, the study analyzes the Compilation of Islamic Law (KHI) alongside its official preparatory documents, legal periodicals, judicial decisions, and relevant regulations from other Muslim-majority jurisdictions. The findings reveal that the construction of wasiat wājibah under Article 209 of the KHI—which grants rights to adopted children and adoptive parents—emerged from an interplay among textual sources of the Sharīʿah (Islamic law), local ʿurf (custom) practices, and the maqāṣid al-sharīʿah (objectives of Islamic law) framework. This construction synthesizes naṣṣ (Qurʾān and hadith), customary adoption traditions, the views of Ibn Ḥazm, and legal precedents from Egypt and Morocco, as reflected in each stage of the KHI’s formulation. The study argues that wasiat wājibah functions as a legal instrument that is adaptive, progressive, and responsive to the demands of substantive justice in Indonesia’s plural Muslim society. It further recommends developing wasiat wājibah models to accommodate marginalized groups excluded from inheritance distribution while preserving the integrity of the foundational principles of the Sharīʿah.